PITPNA-AS1 Inhibits Cell Proliferation and Migration in Ovarian Cancer by Regulating the MIR-223-3p/RHOB Axis - Fei Zhang; Mi Zhang; Zhen Chen; Bo Yu; Xiaoqin He; Yongfang Luo; Fen Ai; Wenfeng Hu (Permanyer, 2024)
Background: Ovarian cancer is a fatal gynecologic malignancy. Long non-coding RNA (lncRNA) has been verified to serve as key regulator in ovarian cancer tumorigenesis. Objective: The aim of the study was to study the functions and mechanism of lncRNA PITPNA-AS1 in ovarian cancer cellular process. Methods: Clinical ovarian cancer samples were collected and stored at an academic medical center. Cellular fractionation assays and fluorescence in situ hybridization were conducted to locate PITPNA-AS1 in OC cells. TUNEL staining, colony-forming assays, and Transwell assays were performed for evaluating cell apoptosis as well as proliferative and migratory abilities. Western blot was conducted for quantifying protein levels of epithelialmesenchymal transition markers. The binding relation between genes was verified by RNA pulldown, RNA immunoprecipitation, and luciferase reporter assays. Gene expression levels in ovarian cancer tissues and cells were subjected to RT-qPCR. Results: PITPNA-AS1 level was downregulated in ovarian cancer samples and cells. PITPNA-AS1 overexpression contributed to the accelerated ovarian cancer cell apoptosis and inhibited cell migration, proliferation, and epithelial-mesenchymal transition process. In addition, PITPNA-AS1 interacted with miR-223-3p to regulate RHOB. RHOB knockdown partially counteracted the repressive impact of PITPNA-AS1 on ovarian cancer cell activities. Conclusion: PITPNA-AS1 inhibited ovarian cancer cellular behaviors by targeting miR-223-3p and regulating RHOB